Pentingnya Pengembangan Keterampilan Soft Skill Dalam Administrasi Perkantoran - Yana Arista Rosi (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
Developing soft skills in office administration has a role in increasing workforce effectiveness and productivity. Soft skills, such as communication skills, and team collaboration are the keys to success in a dynamic work environment. In the context of office administration, strong interpersonal skills can facilitate smooth communication between staff and clients, improve customer service, and strengthen internal company relationships. Additionally, the ability to manage time, resolve conflict, and adapt to change supports issues required in an ever-evolving business environment. By prioritizing soft skills development, companies can ensure that administrative staff have the skills needed to face challenges in carrying out their daily duties. Developing soft skills can also be done through training and experience in physical activities. Employees who are proficient in administrative skills can help the company achieve its mission and vision. Therefore, developing soft skills in the office can increase productivity in the workplace.